Tinjauan Sistem Pengelolaan Data Barang pada Bagian Storekeeper di Harris Hotel & Convention Ciumbuleuit Bandung - Ade Ponirah; Yogi Prastiandi; Fifit Hadiaty (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyze the review of the goods data management system in the storekeeper section at Harris Hotel & Convention Ciumbuleuit Bandung. This study uses a descriptive quantitative method with the aim of describing the goods data management system in the storekeeper. Primary data was obtained through the distribution of a questionnaire with a Likert scale to 30 respondents. The results of the study show that the goods data management system at Harris Hotel & Convention Ciumbuleit Bandung, it can be concluded that the implementation of the goods data management system, this system has been implemented well, as evidenced by the average value of 4,345 which shows that the system is running well in facilitating various processes, such as stock monitoring, goods data management, and procurement of goods. The use of this system simplifies the process of managing goods efficiently, reduces recording errors, and speeds up the procurement process. The obstacles faced are that even though this system has run well, there are several obstacles in its implementation, such as data input errors, limited human resources, limited technological infrastructure, difficulties in adapting to system changes, and data security problems. In an effort to overcome the obstacles faced, strategic steps are needed such as providing regular training to system users in order to minimize data input errors, increase and improve the competence of the human resources involved, and strengthen the technology infrastructure with more adequate devices and networks.